Postpartum Obesity Awakening in LMICs - Pivadga, Collins; Ukaigwe , Patricia C.; Dr. EKPAH, DANIEL (Student’s Journal of Health Research Africa, 2025)
Maternal obesity, excessive gestational weight gain (GWG) and post-partum weight retention (PPWR) constitute new public health challenges due to its association with negative short- and long-term maternal and neonatal outcomes. However, attention appears to be concentrated on developed countries with little/none to developing countries as most developing countries are still scarred by the after-mark of undernutrition and believe obesity is for the affluent. The burden of PPWR on developing countries is unrealistic due to absence of statistical data. There is a popular understanding that pregnancy is a period of rapid weight gain and change in body composition as maternal metabolism adapt to meet the demands of the developing fetus. But how much weight gain is recommended is still arguable among majority of the midwives and among women of childbearing age. PPWR can induce a vicious cycle of gestational obesity through out the reproductive life of a woman predisposing her to all sorts of obstetric complications. As a modifiable risk factor, body weight during the prepregnancy, intranatal, and postpartum periods may present critical windows to apply interventions to prevent weight retention and the development of overweight and obesity in women of childbearing age.